Flame-retardant polymer electrolyte membrane and preparation method thereof

The nanofiber membrane is prepared through electrospinning technology and coated with a synergistic flame retardant, which solves the problem of insufficient flame retardant and electrochemical stability of traditional electrolyte membranes, and realizes a high-performance flame retardant polymer electrolyte membrane, which is suitable for high-safe energy storage equipment.

CN119890465APending Publication Date: 2025-04-25SHENZHEN NO 1 FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070801.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The liquid organic electrolyte used in existing lithium-ion batteries and solid-state batteries has safety risks such as poor thermal safety performance and flammability, and the flame retardancy, mechanical strength and electrochemical stability of traditional polymer electrolyte membranes are insufficient.

Method used

Electrospinning technology is used to prepare nanofiber membranes, and the surface is coated with flame retardant containing hexaphenoxycyclotriphosphazene and diphenylphosphonate to form a gas-phase-condensation phase synergistic flame retardant system to improve the flame retardant and electrochemical properties of the membrane.

Benefits of technology

The film has achieved a balance of excellent flame retardant properties, electrochemical properties, mechanical properties and thermal response properties, and is suitable for energy storage equipment and flexible electronic equipment with high safety requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a flame-retardant polymer electrolyte membrane and a preparation method thereof, and belongs to the technical field of electrolyte materials. The PVDF and PAN composite substrate is adopted, a conductive system of the lithium salt and the ionic liquid is combined, and the synergistic flame retardants hexaphenoxy cyclotriphosphazene and diphenyl phosphonate are added, so that a gas phase-condensed phase synergistic flame-retardant system is formed, the oxygen index of the film is effectively improved, and the heat release rate is reduced. Through structural design and material optimization, the balance among the flame retardant property, the electrochemical property, the mechanical property and the environmental adaptability is realized, and the material has important significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolyte materials, and in particular to a flame-retardant polymer electrolyte membrane and a preparation method thereof. Background Art

[0002] Most of the existing lithium-ion batteries and solid-state batteries use liquid organic electrolytes, which have safety hazards such as poor thermal safety and flammability. In addition, although traditional polymer electrolyte membranes have good electrical conductivity, their flame retardancy, mechanical strength and electrochemical stability still have room for improvement. Therefore, there is an urgent need for a high-performance polymer electrolyte membrane that has both good flame retardancy and optimized ionic conductivity, especially in battery applications with high temperature and high safety requirements. Summary of the invention

[0003] The object of the present invention is to provide a flame-retardant polymer electrolyte membrane and a preparation method thereof, so as to solve the technical problems of insufficient mechanical properties, flame retardancy and electrochemical stability of the electrolyte membrane in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a flame retardant polymer electrolyte membrane, comprising the following steps:

[0006] Step 1), mixing polyvinylidene fluoride, polyacrylonitrile and ethanol solution, and electrospinning the obtained mixed solution to obtain a nanofiber membrane;

[0007] Step 2), adding a flame retardant to the copolymer slurry of methyl methacrylate and styrene, coating the resulting mixture on the surface of the nanofiber membrane after stirring, and sequentially performing drying, activation, and heat treatment to obtain a polymer electrolyte membrane;

[0008] The flame retardant includes hexaphenoxy cyclotriphosphazene and / or diphenylphosphonate.

[0009] Furthermore, in step 1), the mass ratio of polyvinylidene fluoride to polyacrylonitrile is 1-2:2-5;

[0010] The volume ratio of ethanol to water in the ethanol solution is 60-75:25-40.

[0011] Furthermore, in step 1), the concentration of the mixed solution is 10-20 wt%.

[0012] Furthermore, in step 1), the voltage of the electrospinning is 15-20 kV, the injection rate is 0.5-1 mL / h, and the distance is 13-17 cm.

[0013] Furthermore, in step 2), the mass ratio of methyl methacrylate to styrene is 85-90:15-10;

[0014] The mass of the flame retardant is 5-10wt% of the copolymer slurry.

[0015] Furthermore, in step 2), the drying temperature is 50-70° C., and the drying time is 10-15 hours.

[0016] Furthermore, in step 2), the activation is performed by soaking in an electrolyte;

[0017] The electrolyte contains a conductive additive and a solvent;

[0018] The conductive additive includes one or more of LiPF6, LiF and LiTFSI;

[0019] The solvent includes ethylene carbonate.

[0020] Further, the concentration of the electrolyte is 0.8 to 1.5 M;

[0021] The volume ratio of the conductive additive to the solvent in the electrolyte is 1-2:1-3.

[0022] Furthermore, in step 2), the heat treatment temperature is 100-150° C. and the time is 1-4 hours.

[0023] The present invention also provides a flame-retardant polymer electrolyte membrane prepared by the above preparation method.

[0024] Beneficial effects of the present invention:

[0025] 1) Excellent flame retardant performance

[0026] By adding synergistic flame retardants hexaphenoxy cyclotriphosphazene (HPCTP) and diphenylphosphonate (DPP), a gas phase-condensed phase synergistic flame retardant system was formed, which effectively improved the oxygen index (LOI) of the film and reduced the heat release rate (HRR). In the flame retardant test, the film showed LOI ≥ 28%, and UL-94 reached V-0 level, showing good flame retardant properties, suitable for energy storage devices with high safety requirements.

[0027] 2) Excellent electrochemical performance

[0028] The PVDF and PAN composite substrate is combined with a conductive system of lithium salt (LiPF6, LiTFSI) and ionic liquid to give the membrane high ion mobility and electrochemical stability. The ionic conductivity of the membrane is 1.5×10 -3 S / cm, at 50°C, it reaches 2.1×10 -3S / cm, meeting the needs of high-performance lithium-ion batteries and other energy storage devices.

[0029] 3) High mechanical properties and dimensional stability

[0030] The nanofiber membrane substrate is made of PVDF and PAN composite, and its high molecular weight (300000-700000 g / mol of PVDF and 80000-150000 g / mol of PAN) enhances the tensile strength and elongation at break of the membrane. Tests show that the tensile strength of the membrane reaches 50MPa, the elongation at break is 25%, and the mechanical strength retention rate under repeated bending and external force is more than 90%, which is suitable for flexible electronic device applications.

[0031] 4) Excellent thermal response performance

[0032] The thermal response layer (PVA and Li2CO3 blended layer) has good dimensional stability and thermal expansion coefficient control ability. The dimensional change of the film at 50°C does not exceed 3%, showing high adaptability to ambient temperature changes and avoiding device failure.

[0033] 5) Environmental protection and sustainability

[0034] The use of ethanol / water green solvents instead of traditional organic solvents (such as DMF) significantly reduces environmental pollution during the production process and reduces the cost of waste liquid treatment. The selection of flame retardants and base materials meets environmental protection requirements and has better recyclability and low carbon properties.

[0035] 6) Easy to process, suitable for industrial production

[0036] The nanofiber membrane is prepared by electrospinning technology, and the process parameters (voltage, working distance, injection rate) are controllable, ensuring the uniformity of the fiber and the adjustability of the pore structure (porosity 45%, pore size 200-300nm). The heat treatment and coating process are simple, the production efficiency is high, and it is suitable for large-scale preparation.

[0037] 7) Wide range of applications

[0038] This flame-retardant polymer electrolyte membrane has multiple functions such as flame retardancy, conductivity, and mechanical reinforcement. It can be widely used in energy storage devices such as lithium-ion batteries and lithium metal batteries, flexible electronic devices (such as wearable devices), and electrochemical energy equipment with high safety requirements (such as aerospace and new energy vehicles).

[0039] It can be seen that the present invention achieves a balance between flame retardant properties, electrochemical properties, mechanical properties and environmental adaptability through structural design and material optimization, has significant technical innovation and practical value, and meets environmental protection and industrialization needs, providing a new technical solution for the research and development and application of flame-retardant polymer electrolyte membranes. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a flame retardant polymer electrolyte membrane, comprising the following steps:

[0041] Step 1), mixing polyvinylidene fluoride, polyacrylonitrile and ethanol solution, and electrospinning the obtained mixed solution to obtain a nanofiber membrane;

[0042] Step 2), adding a flame retardant to the copolymer slurry of methyl methacrylate and styrene, coating the resulting mixture on the surface of the nanofiber membrane after stirring, and sequentially performing drying, activation, and heat treatment to obtain a polymer electrolyte membrane;

[0043] The flame retardant includes hexaphenoxy cyclotriphosphazene and / or diphenylphosphonate.

[0044] In the present invention, the flame retardant preferably includes hexaphenoxy cyclotriphosphazene and diphenylphosphonate.

[0045] In the present invention, the mass ratio of the hexaphenoxy cyclotriphosphazene to diphenylphosphonate is 1 to 3:1, preferably 2:1.

[0046] In the present invention, hexaphenoxy cyclotriphosphazene mainly forms a protective carbon layer at high temperature, and diphenylphosphonate provides a gas phase flame retardant effect at low temperature. The combination of the two can form a gas phase-condensed phase synergistic flame retardant system to achieve more efficient flame retardant performance. Through the above dosage ratio design, a balance can be achieved between flame retardant performance and mechanical properties of the film to meet application requirements.

[0047] In the present invention, in step 1), the mass ratio of polyvinylidene fluoride to polyacrylonitrile is 1-2:2-5, preferably 1.5:3;

[0048] The volume ratio of ethanol to water in the ethanol solution is 60-75:25-40, preferably 65-70:30-35, and more preferably 68:34.

[0049] In the present invention, the weight average molecular weight of the polyvinylidene fluoride is 3×10 5 ~7×10 5 g / mol, preferably 4×10 5 ~6×10 5 g / mol. High molecular weight PVDF can improve the mechanical strength of the membrane, but medium molecular weight PVDF has better solubility and is suitable for electrospinning.

[0050] In the present invention, the weight average molecular weight of the polyacrylonitrile is 8×10 4 ~1.5×10 5 g / mol, preferably 1×10 5 ~1.3×105 g / mol, higher molecular weight PAN can improve the mechanical properties and thermal stability of the nanofiber membrane, but it may increase the difficulty of dissolution and is not conducive to spinning molding.

[0051] In the present invention, a balance is achieved between the processability, mechanical properties and electrochemical properties of the membrane by reasonably selecting the molecular weight range of polyvinylidene fluoride and polyacrylonitrile.

[0052] In the present invention, the ethanol / water is used as a mixed solvent, which has low toxicity, renewability, simple waste liquid treatment, and multiple advantages such as environmental protection, solubility, economy and safety. It also has a unique role in membrane formation and fiber structure optimization, and is suitable for preparing flame-retardant polymer electrolyte membranes.

[0053] In the present invention, ethanol can weaken the hydrogen bonds between PVDF and PAN molecules and help dissolution; water can reduce the viscosity of the system and facilitate mixing and spinning; the mixture of ethanol and water can adjust the volatilization rate of the solvent, making the volatilization of the solvent more uniform during the electrospinning process, and avoiding pore defects or breakage of the fibers during the spinning process; the polarity and volatilization rate of the mixed solvent work synergistically, making the nanofibers formed during the spinning process more uniform, improving the fiber morphology, and promoting the uniform formation of the nanofibers; it helps to control the fiber diameter and pore distribution, and improve the microstructure of the electrolyte membrane.

[0054] In the present invention, in step 1), the concentration of the mixed solution is 10-20wt%, preferably 12-18wt%, and more preferably 15wt%.

[0055] In the present invention, in step 1), the voltage of the electrospinning is 15-20 kV, preferably 16-18 kV, and more preferably 17 kV, the injection rate is 0.5-1 mL / h, preferably 0.7-0.9 mL / h, and more preferably 0.8 mL / h, and the distance is 13-17 cm, preferably 14-16 cm, and more preferably 15 cm.

[0056] In the present invention, in step 2), the mass ratio of methyl methacrylate to styrene is 85-90:10-15, preferably 87:13;

[0057] The mass of the flame retardant is 5-10wt% of the copolymer slurry, preferably 7-9wt%, and more preferably 8wt%.

[0058] In the present invention, in step 2), the drying temperature is 50-70°C, preferably 55-65°C, more preferably 60°C, and the drying time is 10-15h, preferably 12-14h, more preferably 13h.

[0059] In the present invention, in step 2), the activation is performed by soaking in an electrolyte;

[0060] The electrolyte contains a conductive additive and a solvent;

[0061] The conductive additive includes one or more of LiPF6, LiF and LiTFSI, preferably LiPF6, LiF or LiTFSI, and more preferably LiPF6;

[0062] The solvent comprises ethylene carbonate, preferably ethylene carbonate.

[0063] In the present invention, the soaking time is 1 to 3 hours, preferably 2 hours.

[0064] In the present invention, the concentration of the electrolyte is 0.8 to 1.5 M, preferably 1 to 1.3 M, and more preferably 1.2 M;

[0065] The volume ratio of the conductive additive to the solvent in the electrolyte is 1-2:1-3, preferably 1.2-1.8:1.5-2.5, and more preferably 1.5:2.

[0066] In the present invention, in step 2), the coating amount of the mixture is preferably 0.2 to 0.5 mg / cm 2 , more preferably 0.4 mg / cm 2 .

[0067] In the present invention, in step 2), the heat treatment temperature is 100-150°C, preferably 110-140°C, more preferably 120°C, and the time is 1-4h, preferably 2-3h, more preferably 2.5h.

[0068] The present invention also provides a flame-retardant polymer electrolyte membrane prepared by the above preparation method.

[0069] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] 1 part of polyvinylidene fluoride and 3 parts of polyacrylonitrile were mixed in a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 70:30) to obtain a mixed solution with a concentration of 14 wt%. The obtained mixed solution was electrospun at a voltage of 16 kV, an injection rate of 0.5 mL / h, and a distance of 16 cm to obtain a nanofiber membrane;

[0072] Methyl methacrylate and styrene were mixed in a mass ratio of 87:13, 5 wt% of flame retardant (hexaphenoxy cyclotriphosphazene and diphenylphosphonate in a mass ratio of 2:1) was added, stirred evenly, and then heated to 0.5 mg / cm 2 The coating amount was coated on the surface of the nanofiber membrane, followed by drying at 60°C for 12h, immersing in a 1M LiPF6 / EC electrolyte for activation for 2h, and finally heating the activated membrane at 120°C for 2h to obtain a flame retardant polymer electrolyte membrane.

[0073] Example 2

[0074] 2 parts of polyvinylidene fluoride and 2 parts of polyacrylonitrile were mixed in a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 60:40), and the resulting mixture was electrospun under the conditions of voltage of 15 kV, injection rate of 0.5 mL / h, and distance of 13 cm to obtain a nanofiber membrane;

[0075] Methyl methacrylate and styrene were mixed in a mass ratio of 85:15, 10 wt% of flame retardant (hexaphenoxy cyclotriphosphazene and diphenylphosphonate in a mass ratio of 2:1) was added, stirred evenly, and then heated to 0.5 mg / cm 2 The coating amount was coated on the surface of the nanofiber membrane, and then dried at 70°C for 10 h, immersed in a 1M LiF / EC electrolyte solution for activation for 2 h, and finally the activated membrane was heated at 100°C for 4 h to obtain a flame-retardant polymer electrolyte membrane.

[0076] Example 3

[0077] 1 part of polyvinylidene fluoride and 5 parts of polyacrylonitrile were mixed in a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 75:25), and the resulting mixture was electrospun under the conditions of voltage of 20 kV, injection rate of 1 mL / h, and distance of 17 cm to prepare a nanofiber membrane;

[0078] Methyl methacrylate and styrene were mixed in a mass ratio of 90:10, and 7 wt% of flame retardant (hexaphenoxy cyclotriphosphazene and diphenylphosphonate in a mass ratio of 2:1) was added and stirred evenly. 2 The coating amount was coated on the surface of the nanofiber membrane, followed by drying at 70°C for 10 h, immersing in a 1.5 M LiTFSI / EC electrolyte for activation for 2 h, and finally heating the activated membrane at 150°C for 1 h to obtain a flame retardant polymer electrolyte membrane.

[0079] The flame-retardant polymer electrolyte membrane obtained in Example 1 was subjected to performance tests.

[0080] 1. Flame retardant performance test

[0081] 1.1 Oxygen Index (LOI) Test

[0082] 1) Test equipment: oxygen index meter.

[0083] 2) Test method: Cut a film sample of standard size (100mm×10mm×1mm), test it according to ASTM D2863 standard, gradually adjust the ratio of oxygen and nitrogen around the sample, and record the minimum oxygen volume fraction (i.e. oxygen index) required for the sample to maintain combustion.

[0084] 3) Result analysis: LOI ≥ 28% indicates excellent flame retardant properties.

[0085] 1.2UL-94 vertical burning test

[0086] 1) Test equipment: UL-94 combustion tester.

[0087] 2) Test method: Cut a film sample with a size of 125 mm × 13 mm × 1 mm, fix the sample vertically according to the UL-94 standard, ignite it with a Bunsen burner for 10 seconds, and observe the extinguishing time, dripping, and whether the cotton is ignited.

[0088] 3) Result analysis: The sample reached V-0 grade, indicating excellent flame retardant performance.

[0089] 1.3 Heat release rate (HRR) test

[0090] 1) Testing equipment: Cone Calorimeter.

[0091] 2) Test method: Fix the film sample on the sample tray and place it under the radiation plate of the cone calorimeter. According to ISO5660 standard, test the heat release rate of the sample when it is heated and burned, and record the peak heat release rate (PHRR) and total heat release (THR).

[0092] 3) Result analysis: Low PHRR and THR values ​​indicate good flame retardant properties.

[0093] 2. Electrochemical performance test

[0094] 2.1 Ionic conductivity test

[0095] 1) Test equipment: impedance analyzer.

[0096] 2) Test method: The membrane is sandwiched between stainless steel symmetrical electrodes to form a symmetrical battery structure; -2 Hz to 10 6 AC impedance test is performed in the Hz frequency range;

[0097] The ionic conductivity is calculated by the following formula: σ = d / (Rs × A)

[0098] σ: ionic conductivity (S / cm);

[0099] d: film thickness (cm);

[0100] Rs: impedance (Ω);

[0101] A: Electrode area (cm 2 ).

[0102] 3) Result analysis: Ionic conductivity at room temperature ≥ 1.5×10 -3 S / cm, ≥2.1×10 at 50℃ -3 S / cm.

[0103] 2.2 Electrochemical stability window

[0104] 1) Test equipment: electrochemical workstation.

[0105] 2) Test method: Use the membrane as a separator, assemble a stainless steel / lithium battery, perform a linear sweep voltammetry (LSV) test in the voltage range of 0 to 6 V, record the change of current with voltage, and determine the electrochemical stability window.

[0106] 3) Result analysis: A stability window ≥ 4.5V indicates suitability for high voltage applications.

[0107] 3. Mechanical properties test

[0108] 3.1 Tensile strength and elongation at break

[0109] 1) Testing equipment: Universal testing machine (such as Instron 3365).

[0110] 2) Test method: According to ASTM D882, cut a standard dumbbell-shaped sample, clamp the sample, test the tensile rate at 10 mm / min, and record the force and elongation at break.

[0111] 3) Result analysis: tensile strength ≥50MPa, elongation at break ≥25%.

[0112] 3.2 Anti-fatigue performance

[0113] 1) Testing equipment: bending tester.

[0114] 2) Test method: The film was bent repeatedly (bending radius 10 mm) 100 times, the tensile strength was retested, and the retention rate was calculated.

[0115] 3) Result analysis: Mechanical strength retention rate ≥ 90%.

[0116] 4. Thermal response performance test

[0117] 1) Test equipment: Dynamic Mechanical Analyzer (DMA).

[0118] 2) Test method: Place the film in a temperature-controlled environment (temperature range: 25°C to 50°C), use DMA to test the coefficient of thermal expansion (CTE) and dimensional change of the film, and record the dimensional change rate of the film.

[0119] 3) Result analysis: Within the temperature change range, the dimensional change is ≤3%.

[0120] 5. Environmental adaptability test

[0121] 5.1 Temperature adaptability

[0122] 1) Test equipment: battery test system (such as LAND system).

[0123] 2) Test method: Test Li|LiFePO4 batteries at 0.5C rate, test battery capacity retention at -20℃ and 60℃, and record the impact of temperature changes on battery performance.

[0124] 3) Result analysis: -20℃ capacity retention rate ≥85%, 60℃ capacity retention rate ≥95%.

[0125] 5.2 Pressure adaptability

[0126] 1) Test equipment: pressure simulator.

[0127] 2) Test method: Simulate the local pressure (0.1MPa~0.5MPa) when worn by the human body, and observe the changes in the size and mechanical properties of the membrane.

[0128] 3) Result analysis: Dimension change ≤ 2%.

[0129] 6. Thermogravimetric analysis test

[0130] 1) Test purpose: To analyze the thermal stability and decomposition behavior of flame-retardant polymer electrolyte membranes and to evaluate the effect of flame retardants in the membranes on thermal degradation.

[0131] 2) Test equipment

[0132] Equipment model: Thermogravimetric analyzer (such as TAInstruments TGAQ50 or MettlerToledo TGA / DSC).

[0133] 3) Test environment:

[0134] Nitrogen atmosphere (inert environment) or air atmosphere (oxidizing environment);

[0135] Gas flow rate: 20~50mL / min.

[0136] 4) Sample preparation

[0137] A uniform sample of about 5 to 10 mg is cut from the flame-retardant polymer electrolyte membrane to ensure that the sample is free of impurities or moisture contamination (the sample needs to be dried at 60° C. for 4 hours to remove adsorbed moisture).

[0138] 5) Test steps

[0139] Sample weighing: accurately weigh the sample and place it in a TGA platinum crucible;

[0140] Sample mass range: 5-10 mg, ensuring test sensitivity.

[0141] Temperature program settings: starting temperature: room temperature (25°C); heating rate: 10°C / min; ending temperature: 800-1000°C.

[0142] Atmosphere setting:

[0143] Nitrogen atmosphere: used to study the thermal decomposition characteristics of polymers and flame retardants;

[0144] Air atmosphere: used to evaluate the antioxidant properties and carbon residue rate of flame retardants.

[0145] Data recording: Real-time recording of sample mass changes (temperature as the horizontal axis and sample mass percentage as the vertical axis).

[0146] 6) Data analysis

[0147] Key parameters:

[0148] Initial decomposition temperature (T0): the temperature at which the sample begins to lose mass;

[0149] Maximum weight loss rate temperature (Tmax): the temperature corresponding to the highest point of mass loss rate;

[0150] Residual carbon rate: the mass percentage remaining at 800-1000℃, reflecting the carbonization effect of the flame retardant.

[0151] Interpretation of results: The higher the initial decomposition temperature, the better the thermal stability, and the higher the residual carbon rate indicates that the flame retardant has a good condensed phase protection effect.

[0152] 7) Thermogravimetric analysis description

[0153] Initial decomposition temperature (T0): 280℃;

[0154] Maximum weight loss rate temperature (Tmax): 350℃;

[0155] Residual carbon rate: 20% (at 800°C).

[0156] In addition, compared with the membrane without added flame retardant, the initial decomposition temperature of the membrane increased by 30°C and the residual carbon rate increased by 10% after adding hexaphenoxy cyclotriphosphazene and diphenylphosphonate, proving that the flame retardant effectively improved the thermal stability of the membrane.

[0157] 8) Reference standards: ASTM E1131: "Standard test method for analysis of polymeric materials by thermogravimetric analysis"; ISO 11358-1: "Standard method for thermogravimetric analysis of polymers".

[0158] It can be seen from the above embodiments that the present invention provides a flame-retardant polymer electrolyte membrane and a method for preparing the same. The present invention achieves a balance between flame retardancy, electrochemical properties, mechanical properties and environmental adaptability through structural design and material optimization, has significant technical innovation and practical value, and meets environmental protection and industrialization requirements, providing a new technical solution for the research and development and application of flame-retardant polymer electrolyte membranes, and solving the technical problems of insufficient mechanical properties, flame retardancy and electrochemical stability of electrolyte membranes in the prior art.

[0159] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a flame-retardant polymer electrolyte membrane, characterized in that: The following steps are involved: Step 1), mixing polyvinylidene fluoride, polyacrylonitrile and ethanol solution, and electrospinning the obtained mixed solution to obtain a nanofiber membrane; Step 2), adding a flame retardant to the copolymer slurry of methyl methacrylate and styrene, coating the resulting mixture on the surface of the nanofiber membrane after stirring, and sequentially performing drying, activation, and heat treatment to obtain a polymer electrolyte membrane; The flame retardant includes hexaphenoxy cyclotriphosphazene and / or diphenylphosphonate.

2. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 1, characterized in that: In step 1), the mass ratio of polyvinylidene fluoride to polyacrylonitrile is 1-2:2-5; The volume ratio of ethanol to water in the ethanol solution is 60-75:25-40.

3. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 1 or 2, characterized in that: In step 1), the concentration of the mixed solution is 10-20 wt%.

4. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 3, characterized in that: In step 1), the voltage of the electrospinning is 15-20 kV, the injection rate is 0.5-1 mL / h, and the distance is 13-17 cm.

5. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 1, 2 or 4, characterized in that: In step 2), the mass ratio of methyl methacrylate to styrene is 85-90:10-15; The mass of the flame retardant is 5-10wt% of the copolymer slurry.

6. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 5, characterized in that: In step 2), the drying temperature is 50-70° C. and the drying time is 10-15 hours.

7. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 1, 4 or 6, characterized in that: In step 2), the activation is performed by soaking in an electrolyte; The electrolyte contains a conductive additive and a solvent; The conductive additive includes one or more of LiPF6, LiF and LiTFSI; The solvent includes ethylene carbonate.

8. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 7, characterized in that: The concentration of the electrolyte is 0.8 to 1.5 M; The volume ratio of the conductive additive to the solvent in the electrolyte is 1-2:1-3.

9. The method for preparing a flame-retardant polymer electrolyte membrane according to claim 2, characterized in that: In step 2), the heat treatment temperature is 100-150° C. and the time is 1-4 hours.

10. The flame-retardant polymer electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8.